PERTUMBUHAN TINGGI DAN DIAMETER TANAMAN JATI SALOMON (Tectona grandis Linn.f.) UMUR 11 TAHUN DI DESA TANAH MERAH - Herijanto Thamrin (JURNAL AGRIMENT, 2019)
The purpose of this study was to grow the height and diameter of the Solomon Teak tree (Tectona grandis) planted in 2006 on Samarinda-Bontang Street, Tanah Merah Village, North Samarinda District. The results of this study were able to provide information about the growth of Teak Solomon's height and diameter at that location and as input for the development of Solomon Teak plants, especially in East Kalimantan.The research method used is a simple random method to get 100 trees to be studied. Selected trees measured their height and diameter then analyzed with simple statistics.Based on the results of calculations, data analysis and discussion, it can be concluded that the growth of the average height and diameter of the Salomon Teak Jalan Poros Samarinda - Bontang is equal to 17.621 m for height and an average diameter of 19.246 cm. Growth is better than ordinary teak species (Perhutani) located in East Kutai. It is recommended for young teak plants to be maintained more intensively so that the adaptation process will quickly occur and minimize competition. Another factor that needs to be considered is doing mixcropping with annual plants considering the width of the spacing used